A new species of Chrysophyllum (Sapotaceae) from the Brazilian Atlantic forest - Sossai, Brenno Gardiman; Viégas-Aquije, Glória; Santos, Francisco De Assis Ribeiro Dos; Alves-Araújo, Anderson (Phytotaxa, 2017)
The new species Chrysophyllum pubipetalum from the Brazilian Atlantic forest of Espírito Santo state is described and illustrated. This new species is characterized by the presence of trichomes on both surfaces of the corolla (a character unique in the genus), channeled petioles, a relatively short pedicel length, and various characters of the fruits and seeds. A distribution map and a table distinguishing the new species from morphologically similar species are also included. As based on IUCN criteria, the species is considered critically endangered.